VMware vSphere 4 administration instant reference - Lowe, Scott 1970- (Wiley, 2010)
"Get all your solutions about VMware's newest virtualization infrastructure software on the spot with this handy reference guide. Designed for quick access with special headings, thumb tabs, easy-to-read lists, and more, this book is the perfect companion to any comprehensive VMware guide, such as Mastering VMware vSphere 4"--Resource description page.
Print version record
Keywords: VMware; Virtual computer systems; Operating systems (Computers); Systèmes virtuels (Informatique); Systèmes d'exploitation (Ordinateurs); operating systems